2018
DOI: 10.1007/s00392-018-1282-7
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-disordered breathing in patients with cardiovascular diseases cannot be detected by ESS, STOP-BANG, and Berlin questionnaires

Abstract: Sleep-disordered breathing (SDB) is highly prevalent in patients with cardiovascular diseases (CVD) and associated with poor outcome. At least 50% of heart failure (HF) patients present with SDB, equally divided in obstructive sleep apnea (OSA) and central sleep apnea (CSA). CVD patients with SDB do not always present with typical SDB symptoms. Therefore, we asked whether established questionnaires allow for the reliable detection of SDB. In this prospective cohort study, 89 CVD patients (54 male, 59 ± 15 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 53 publications
2
28
0
9
Order By: Relevance
“…Age, BMI, ESS, peak level of troponin and use of calcium antagonists were all associated with OSA, but no statistical model allowed prediction of OSA [65]. This confirms data from REUTER et al [66] in stable patients with chronic cardiovascular diseases. They found that the STOP-BANG and Berlin questionnaires did not reliably detect or exclude SDB in patients with cardiovascular diseases.…”
Section: Diagnosis Of Sleep Disturbances Risk Factors Predictors Ansupporting
confidence: 66%
“…Age, BMI, ESS, peak level of troponin and use of calcium antagonists were all associated with OSA, but no statistical model allowed prediction of OSA [65]. This confirms data from REUTER et al [66] in stable patients with chronic cardiovascular diseases. They found that the STOP-BANG and Berlin questionnaires did not reliably detect or exclude SDB in patients with cardiovascular diseases.…”
Section: Diagnosis Of Sleep Disturbances Risk Factors Predictors Ansupporting
confidence: 66%
“…Finally, we used the ESS to assess symptom response to therapy. Although the ESS does not reliably predict sleep‐disordered breathing, especially in those with cardiovascular disease (Reuter et al, ), it is a widely used measure of symptom response. In addition, all patients were assessed by clinicians during therapy and ASV was prescribed on the basis of subjective improvement in symptoms and objective control of sleep apnea.…”
Section: Discussionmentioning
confidence: 99%
“…Questionnaires do not accurately predict OSAS in patients with cardio-vascular disease (CVD) [31]. Epworth Sleepiness Scale and SAS score can be beneficial in predicting OSAS, but in our groups of patients, although the values are high, differences between groups are insignificant [32].…”
Section: Discussionmentioning
confidence: 99%